Partisipasi Masyarakat dalam Pelaksanaan Program Peremajaan Sawit Rakyat (PSR) pada Kelompok Tani Sukses Bersama di Nagari Bawan Kecamatan Ampek Nagari Kabupaten Agam - Desi Susanti; M.Fachri Adnan (YASIN, 2026)
The low productivity of smallholder oil palm plantations is influenced by trees that have exceeded their productive age, the use of non-improved seeds, and farmers’ limited capital and technical knowledge. As an effort to address these problems, the government implemented the Smallholder Oil Palm Replanting (PSR) Program through the replanting of ageing trees, supported by grant funding and assistance. The success of this program is strongly influenced by community participation at every stage of its implementation. However, the participation of members of the Sukses Bersama Farmer Group in Nagari Bawan has not been optimal because of economic and administrative constraints and limited technical understanding. This study aimed to analyse the forms of community participation and identify the factors that encouraged and hindered participation in the implementation of the PSR Program. The study employed a qualitative approach using a field research method. Informants were selected purposively and consisted of the head of the farmer group, farmer group members, and nagari officials. Data were collected through interviews, observations, and documentation and were subsequently analysed inductively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that community participation occurred at the planning, implementation, outcome utilization, and evaluation stages, but community involvement in decision-making remained low. Socialization played an important role in improving farmers’ understanding, although its implementation was not evenly distributed. Factors encouraging participation included trust in the farmer group, collaborative networks, and expectations of increased plantation yields. Meanwhile, factors hindering participation included economic constraints during the immature phase of the replanted trees, administrative obstacles, and concerns regarding income sustainability. This study confirms that improving the success of the PSR Program requires strengthened socialization, farmer group institutions, and continuous administrative assistance. These findings provide practical contributions for the nagari government, farmer groups, and relevant stakeholders in designing strategies to increase community participation in the implementation of smallholder plantation replanting programs.